The Influence of Bead Media on Mathematics Learning Outcomes of Grade 1 Elementary School Students - Hartan, Rafiq; Fathoni, Achmad (Euclid, 2023)
Mathematics education plays a very important role. By studying mathematics at the elementary school level, students will have strong basic knowledge of mathematics to study mathematics at the secondary school level.One of the learning materials that must be studied in grade 1 elementary school is addition. The teacher's selection of appropriate learning media for the material to be delivered can influence student learning outcomes. One effort that can be used to make addition material fun and attractive to students is by providing learning media in the form of beads. The research design used in this research is Classroom Action Research Design (PTK). This research was applied to one class with two learning meetings, namely at the first meeting it was taught without using bead media and in the second meeting using learning media in the form of beads. The results obtained are an increase ofthe percentage was 77%, which was previously only 36%. This use of bead media greatly influences the learning outcomes of grade 1 students at SDiT Bit Surakarta.